ALE meta‐analysis reveals dissociable networks for affective and discriminative aspects of touch. Issue 4 (1st February 2016) - Morrison, India
Abstract: Emotionally‐laden tactile stimulation—such as a caress on the skin or the feel of velvet—may represent a functionally distinct domain of touch, underpinned by specific cortical pathways. In order to determine whether, and to what extent, cortical functional neuroanatomy supports a distinction between affective and discriminative touch, an activation likelihood estimate (ALE) meta‐analysis was performed. This meta‐analysis statistically mapped reported functional magnetic resonance imaging (fMRI) activations from 17 published affective touch studies in which tactile stimulation was associated with positive subjective evaluation ( n = 291, 34 experimental contrasts). A separate ALE meta‐analysis mapped regions most likely to be activated by tactile stimulation during detection and discrimination tasks ( n = 1, 075, 91 experimental contrasts). These meta‐analyses revealed dissociable regions for affective and discriminative touch, with posterior insula (PI) more likely to be activated for affective touch, and primary somatosensory cortices (SI) more likely to be activated for discriminative touch. Secondary somatosensory cortex had a high likelihood of engagement by both affective and discriminative touch. Further, meta‐analytic connectivity (MCAM) analyses investigated network‐level co‐activation likelihoods independent of task or stimulus, across a range of domains and paradigms. Affective‐related PI and discriminative‐related SI regions co‐activated with different networks, implicated in dissociable functions, but sharing somatosensory co‐activations. Taken together, these meta‐analytic findings suggest that affective and discriminative touch are dissociable both on the regional and network levels. However, their degree of shared activation likelihood in somatosensory cortices indicates that this dissociation reflects functional biases within tactile processing networks, rather than functionally and anatomically distinct pathways. Hum Brain Mapp 37:1308‐1320, 2016 . © 2016 Wiley Periodicals, Inc.